2022
DOI: 10.3389/fneur.2022.826266
|View full text |Cite
|
Sign up to set email alerts
|

Thalamo-Prefrontal Connectivity Correlates With Early Command-Following After Severe Traumatic Brain Injury

Abstract: Recovery of consciousness after traumatic brain injury (TBI) is heterogeneous and difficult to predict. Structures such as the thalamus and prefrontal cortex are thought to be important in facilitating consciousness. We sought to investigate whether the integrity of thalamo-prefrontal circuits, assessed via diffusion tensor imaging (DTI), was associated with the return of goal-directed behavior after severe TBI. We classified a cohort of severe TBI patients (N = 25, 20 males) into Early and Late/Never outcome … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Thus, our results appear to be generally in line with the results of the previous fMRI and DTT-based studies mentioned above [11–19,23]. However, to the best of our knowledge, this is the first study to demonstrate the relationship between the consciousness level and the mPFC SNC in patients with HI-BI.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, our results appear to be generally in line with the results of the previous fMRI and DTT-based studies mentioned above [11–19,23]. However, to the best of our knowledge, this is the first study to demonstrate the relationship between the consciousness level and the mPFC SNC in patients with HI-BI.…”
Section: Discussionsupporting
confidence: 92%
“…By using DTT, several case studies have demonstrated that the increased neural connectivity to the mPFC from the thalamic intralaminar nucleus in the ARAS was responsible for the recovery of impaired consciousness in patients with stroke (three patients) and HI-BI (two patients) [11][12][13][14][15]. Recently, Cosgrove et al [23] found that the integrity of the connections between the whole thalamus and the three subregions of the prefrontal cortex (mPFC, anterior cingulate cortex, and orbitofrontal cortex) was associated with the ability to follow commands in 25 patients with severe TBI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifth, we analysed only two tracts of the DMN among various neural networks for control of consciousness [13][14][15][16]19]. As a result, further studies including larger number of subjects and analysing other neural networks for control of consciousness should be encouraged; especially the neural networks including the thalamus which is a center for control of consciousness such as the thalamo-prefrontal connection [35][36][37].…”
Section: Discussionmentioning
confidence: 99%